Revitalizing Religious Moderation in Islamic Education: Strategies for Preventing Radicalism and Building Peace - Rahma, Ainun (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
The phenomenon of increasing radicalism in various levels of society, including in educational environments, poses a serious challenge to building peaceful and harmonious religious life. This condition requires the strengthening of religious moderation values that can be integrated into the education system, particularly Islamic Religious Education (PAI). The revitalization of religious moderation is seen as a strategic step in preventing the development of extremist ideologies that have the potential to threaten national unity and integrity. This study aims to analyze the concept and strategies of revitalizing religious moderation in education as an effort to prevent radicalism and build a culture of peace. The research method used is qualitative research with a descriptive approach through library research on various scientific literature, books, and government policies related to religious moderation. The results show that religious moderation rooted in the concept of wasathiyah contains values of balance, justice, and tolerance that can suppress the potential for radicalism. On the contrary, radicalism grows as a result of a shallow understanding of religion, narrow interpretation of texts, and a lack of understanding of social realities. In the context of education, strengthening values such as civility, exemplary behavior, citizenship, balance, justice, equality, and tolerance is key to shaping the character of students to be moderate and virtuous. In conclusion, the revitalization of religious moderation in education is not only an effort at deradicalization, but also a foundation for creating a just, civilized, and peace-loving society.